(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
CED is one of the causes of bleeding in pregnant women, the risk of pregnancy complications such as anemia, weight does not increase normally, and infectious diseases. During pregnancy, the mother's hematological system undergoes significant changes. One of them is a 30-50 percent increase in blood plasma, with an average increase of 1.5 liters during pregnancy. This is often referred to as hemodilution, while pregnant women who are at risk of CED have a 2.96 times chance of suffering from anemia compared to pregnant women who are not at risk of CED. The purpose of the study was to determine the effect of giving boiled chicken eggs on hemoglobin levels in pregnant women with CED in the working area of Bontoa Health Center. This type of research is quasi-experimental, using a pretest-posttest control group design. In the post-test experimental group, the average value of hemoglobin levels is 11.51 mg/dl while for the post-test control group the average value of hemoglobin levels is 9.87 mg/dl, the results of the independent statistical test sample test obtained p value = 0.00